Utilización de técnicas grafo – plásticas y material didáctico como estrategia metodológica, y su influencia en el desarrollo de la creatividad de los alumnos del primer año de educación básica de los centros educativos “Siglo XXI” y “Bernardo Valdivieso” de la ciudad de Loja, año lectivo 2008-2009. Lineamientos alternativos - Ayora Fernández, Amable Guillermo (2011)
CT. This research was conducted in the city of Loja, in the 2008-2009 academic year was used as one hundred twenty-eight population students and nine teachers from the First Year of Basic Education that normally attend the Schools "Siglo XXI" and "Bernardo Valdivieso" addresses the problem of using graph techniques - materials such as plastic and methodological strategy and its influence on the development of creativity of students in the first year of basic education schools in the city above Loja, for which we have developed alternative guidelines, this work is aimed primarily at teachers and students to ensure that the guidelines suggested a return to better develop children's creativity. For the elaboration of this theme had to resort to different literature sources, and have tried to compile accurate, clear and simple information material with synthetic approach and the spirit of contribution tends to update the information on graph techniques - plastic and the material for the development of creativity, this approach was the need to elevate the role of persuasion in the educational work which is key to strengthening scientific knowledge aimed at strengthening children's creativity is essential that the need that the work done by educators to be enriched with the implementation and action planning graph - plastic and use of appropriate teaching materials in each of the planned activities to strengthen the development of skills to develop children's creativity with performance criterion . We hope that the work is welcoming anyone interested in this subject in order to contribute to improving the quality of education for all educational communities who form the subject of this work.